Migration in South Asia IMISCOE Regional Reader - Rajan, S. Irudaya (IMISCOE Research Series, 2023)
This open access Regional Reader provides a contemporary look at the emerging challenges and issues facing South Asian migration amidst covid-19 and discusses a framework for a sustainable and cooperative migration from and within the region, which will impact both the economic and regional development of South Asia. The book draws a focus on this area through an interdisciplinary and holistic lens and follows the three broad areas of migration studies in South Asia: Governance and mobility, Family, health and demography, and Forced migration. It thereby covers a number of issues from South Asian countries such as Afghanistan, Bangladesh, Bhutan, India, Nepal, Pakistan and the Maldives. This book is a valuable resource for those who want to understand the dynamics of migration from the largest migrant-sending region in the world and one which will determine the shape of global migration patterns in the future.